Հեմոֆիլային արթրոպաթիաների բուժման տարբեր եղանակների արդյունավետության գնահատականը կյանքի որակի ցուցանիշների օգնությամբ - Հ. Ս. Խաչատրյան; Ս. Ս. Դաղբաշյան; Լ. Ս. Սահակյան (Հայաստանի ԳԱԱ)
В статье проведен анализ эффективности различных методов терапии гемофильных артропатий по показателям качества жизни. Выявлена эффективность химической синовэктомии при гемофильных артропатиях, совпадающая и по показателям клинико-лабораторных исследований. An analysis of the efficiency of different methods of hemophilic arthropathy therapy according to the indicators of life quality has been carried out. The effectiveness of chemical synovectomy at hemophilic arthropathy has been revealed corresponding to the obtained clinical-laboratory data.
Keywords: Medicine